Effect of Warm-Dry Storage and Supplemental Application of Gibberellins on the Lipid Profile of Chincuya Seeds (Annona purpurea Moc. & Sessé ex Dunal) - Vidal-Lezama, Eloísa; Reyes-Trejo, Benito; Villegas-Monter, Ángel; Vaquera-Huerta, Humberto; Robledo-Paz, Alejandrina; Martínez-Palacios, Alejandro; Ferreira, Gisela [UNESP] (MDPI, 2024)
Despite ample knowledge of the effect of warm-dry storage on breaking dormancy in chincuya (Annona purpurea Moc. & Sessé ex Dunal) seeds, this paper investigates an important new aspect of this process—the applicability of seed treatment with gibberellic acid and its influence on seed viability and fatty acid profile. Chincuya is an underutilized, tropical wild species native to Mexico, with potential as a biopesticide. The impact of warm-dry storage and gibberellic acid treatment on seed viability and germination was determined to improve that knowledge further. Also, the content and kinetics of fatty acids in chincuya seeds were profiled during warm-dry storage. Seed treatments included storage time (0, 3, 6, 9, and 12 months), seed imbibition for 72 h in gibberellic acid at 350 mg L−1, and distilled water imbibition for 72 h for the control treatment. Seed viability was determined using the TTZ classic test. Imbibed seeds were germinated on paper towels and incubated at 30 °C during the day and 25 °C at night in a 12:12 h dark/light photoperiod. The lipid profile was obtained by gas chromatography. During the storage treatment, seeds stayed in darkness at 25 ± 3 °C. Results showed that high viability remained up to month 9 in storage when it significantly decreased. Freshly harvested seeds germinated at a statistically significantly lower rate (26.1%) than six-month-old seeds (65.6%). The profile of fatty acids breaks down as palmitic acid (33.41%), stearic acid (7.72%), and arachidic acid (1.30%), for a total of 42.44% of saturated fatty acids. The detected unsaturated fatty acids (52.15%) were palmitoleic acid (1.52%), oleic acid (43.37%), and linoleic acid (7.24%). No significant changes were detected in fatty acid content; however, the highest fatty acid content (92.84%) occurred with the highest germination rate. Regression analysis showed significant content changes: palmitoleic and palmitic acids increased while oleic acid decreased during dry storage. Arachidic acid showed a slight downward trend. Also, fatty acid content significantly differed between intact seeds (unstored and unincubated) and latent seeds (unstored, incubated, and ungerminated). The total fatty acids content for latent seeds was significantly lower. These results show that Annona purpurea seeds present morphophysiological dormancy. Also, we document the highest germination rate reported (65.6%) and report the presence of arachidic and palmitoleic acids in chincuya seeds.
Keywords: after ripening; anona; arachidic acid; development regulators; dormancy; endodormancy; fatty acids; germination; hormonal regulators; latency; linoleic acid; oleic acid; palmitic acid; palmitoleic acid; soncoya; stearic acid